Assessing information sources to elucidate diagnostic process errors in radiologic imaging — a human factors framework. (16th August 2018) - Cochon, Laila; Lacson, Ronilda; Wang, Aijia; Kapoor, Neena; Ip, Ivan K; Desai, Sonali; Kachalia, Allen; Dennerlein, Jack; Benneyan, James; Khorasani, Ramin
Abstract: Objective: To assess information sources that may elucidate errors related to radiologic diagnostic imaging, quantify the incidence of potential safety events from each source, and quantify the number of steps involved from diagnostic imaging chain and socio-technical factors. Materials and Methods: This retrospective, Institutional Review Board-approved study was conducted at the ambulatory healthcare facilities associated with a large academic hospital. Five information sources were evaluated: an electronic safety reporting system (ESRS), alert notification for critical result (ANCR) system, picture archive and communication system (PACS)-based quality assurance (QA) tool, imaging peer-review system, and an imaging computerized physician order entry (CPOE) and scheduling system. Data from these sources (January-December 2015 for ESRS, ANCR, QA tool, and the peer-review system; January-October 2016 for the imaging ordering system) were collected to quantify the incidence of potential safety events. Reviewers classified events by the step(s) in the diagnostic process they could elucidate, and their socio-technical factors contributors per the Systems Engineering Initiative for Patient Safety (SEIPS) framework. Results: Potential safety events ranged from 0.5% to 62.1% of events collected from each source. Each of the information sources contributed to elucidating diagnostic process errors in various steps of the diagnostic imaging chain and contributing socio-technical factors, primarily Person, Tasks, and Tools and Technology . Discussion: Various information sources can differentially inform understanding diagnostic process errors related to radiologic diagnostic imaging. Conclusion: Information sources elucidate errors in various steps within the diagnostic imaging workflow and can provide insight into socio-technical factors that impact patient safety in the diagnostic process.